EFFECTS ON THE SANDF OF - SIBANGO, A.M. (My University, 2011)
The author had observed challenges emanating from active membership of the South African National Defence Force (SANDF) personnel in party politics and labour unions with potential implications of towing the party-political line and, developing much more confidence in union organisation at the expense of the military organisation, which could possibly affect the military either in positive or negative ways. The writer sought to investigate and provide an assessment of the extent to which these phenomena might have effects, especially on the notion of combat readiness. Certain findings were drawn leading to some options as recommended course of action to find answers to the security sector governance and transformation agenda. Of particular note, are suggestions for continuous examination of all attributes that determine the status of combat readiness in the form of surveys with the view to establishing certain trends that would impact negatively to the military discourse, the establishment of the Permanent National Defence Force Service Commission and the introduction of the Office of Ombudsman to deal with all issues related to the conditions of service and any other administrative complaints that confront ordinary soldiers from time to time, respectively
MM - P&DM
Keywords: Trade unions; Military trade unions; South African National Defence Force; Party political affliations